Discovery and Optimization of Small-Molecule Ligands for the CBP/p300 Bromodomains - Hay, D; Fedorov, O; Martin, S; Singleton, D; Tallant, C; Wells, C; Picaud, S; Philpott, M; Monteiro, O; Rogers, C; Conway, S; Rooney, T; et al. (American Chemical Society, 2014)
Small-molecule inhibitors that target bromodomains outside of the bromodomain and extra-terminal (BET) sub-family are lacking. Here, we describe highly potent and selective ligands for the bromodomain module of the human lysine acetyl transferase CBP/p300, developed from a series of 5-isoxazolyl-benzimidazoles. Our starting point was a fragment hit, which was optimized into a more potent and selective lead using parallel synthesis employing Suzuki couplings, benzimidazole-forming reactions, and reductive aminations. The selectivity of the lead compound against other bromodomain family members was investigated using a thermal stability assay, which revealed some inhibition of the structurally related BET family members. To address the BET selectivity issue, X-ray crystal structures of the lead compound bound to the CREB binding protein (CBP) and the first bromodomain of BRD4 (BRD4(1)) were used to guide the design of more selective compounds. The crystal structures obtained revealed two distinct binding modes. By varying the aryl substitution pattern and developing conformationally constrained analogues, selectivity for CBP over BRD4(1) was increased. The optimized compound is highly potent (Kd = 21 nM) and selective, displaying 40-fold selectivity over BRD4(1). Cellular activity was demonstrated using fluorescence recovery after photo-bleaching (FRAP) and a p53 reporter assay. The optimized compounds are cell-active and have nanomolar affinity for CBP/p300; therefore, they should be useful in studies investigating the biological roles of CBP and p300 and to validate the CBP and p300 bromodomains as therapeutic targets.